EVALUASI PROGRAM PENDIDIKAN KESETARAAN PAKET B - Abdul Rahmat (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2013)
The purpose of this research was to discover how the equivalency educational program of B package to support the the nine years compulsory educational program in Gorontalo District. The research conducted as from April 2011 through February 2012, used phenomenology approach and design multi cases. The data were collected using deep interview, participation observation, and documentation study and analysed employing case individual analysis and analysis multy cases. The result of this research is related to the program content, learning and teaching process, program structure, and learning resources.